Scalable, interfacially synthesized, covalent-organic framework (COF)-based thin-film composite (TFC) hollow fiber membranes for organic solvent nanofiltration (OSN) - Kunjattu, Shebeeb H.; Thorat, Nitin M.; Gawas, Saroj; Kharul, Ulhas K. (ACS Applied Materials and Interfaces, 2024)
Covalent organic frameworks have great potential for energy-efficient molecular sieving-based separation. However, it remains challenging to implement COFs as an alternative membrane material due to the lack of a scalable and cost-effective fabrication mechanism. This work depicts a new method for fabricating a scalable in situ COF hollow fiber (HF) membrane by an interfacial polymerization (IP) approach at room temperature. The 2D COF film was constructed on a polyacrylonitrile HF substrate using aldehyde (1,3,5-trimethylphloroglucinol, Tp) and amine (4,4 `-azodianiline (Azo) and 4,4 `,4 `'-(1,3,5-triazine- 2,4,6-triyl) trianiline (Tta)) as precursors. The COF membrane on the PAN substrate showed 99% rejection of Direct red-80 with remarkable solvent permeance. The rejection analysis revealed that the structural aspects of the solute molecule play a major role in rejection rather than the molecular weight. We further optimized the precursor concentrations to improve the permeation performance of the resulting membrane. The durability study reveals excellent stability of the membrane toward organic solvents. This study also demonstrated the easy scalability of the membrane fabrication approach. The approach was further extrapolated to fabricate a cation-based COF membrane. These charged membranes exhibited an enhanced rejection performance. Finally, this approach can facilitate industrially challenging molecular sieving applications using COF-based membranes.
Keywords: covalent-organic framework; hollow fiber; interfacial polymerization; organic solvent nanofiltration; selective COF membrane